CHARACTER EDUCATION MANAGEMENT: ANALYSIS OF CHARACTER-BUILDING AT SMK MUHAMMADIYAH KAJEN - Mirza Mahbub Wijaya; Ahmad Yusuf (Universitas Islam Sultan Agung, 2021)
This study aims to determine the implementation of Islamic education management at SMK Muhammadiyah Kajen. In this case, the researcher used a qualitative method with a phenomenology approach, collecting data through observation, interviews, and documents. In addition, to maintain data accuracy, researchers used data triangulation methods. While the research informants were the principal, teachers, and parents of students. The results of this study indicate that SMK Muhammadiyah Kajen implements: 1) Semangat Subuh, this culture is done to train students to obey congregational prayers and wake up in the morning; 2) Memorizing juz Amma, to get students used to always reading al-Qur'an every day; 3) Pesantren Ramadhan, namely Islamic activities about fikih, akidah akhlak, and sirah nabawiyah. In addition to strengthening student character, Islamic boarding schools are friendly and can also instill a culture of student literacy.Keywords: Character, Islamic Education, Islamic Literacy